Beyond Camelot : rethinking politics and law for the modern state - Rubin, Edward L., 1948- (Princeton University Press, 2005)
This book argues that many of the basic concepts that we use to describe and analyze our governmental system are out of date. Developed in large part during the Middle Ages, they fail to confront the administrative character of modern government. These concepts, which include power, discretion, democracy, legitimacy, law, rights, and property, bear the indelible imprint of this bygone era's attitudes, and Arthurian fantasies, about governance. As a result, they fail to provide us with the tools we need to understand, critique, and improve the government we actually possess. Beyond Camelot expl.